2022
DOI: 10.3390/cancers14051147
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preferences for Treatment Outcomes in Oncology with a Focus on the Older Patient—A Systematic Review

Abstract: For physicians, it is important to know which treatment outcomes are prioritized overall by older patients with cancer, since this will help them to tailor the amount of information and treatment recommendations. Older patients might prioritize other outcomes than younger patients. Our objective is to summarize which outcomes matter most to older patients with cancer. A systematic review was conducted, in which we searched Embase and Medline on 22 December 2020. Studies were eligible if they reported some form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 61 publications
0
27
0
1
Order By: Relevance
“…For distant cancers, the greatest age-related differences in 1-year RS were observed for colon and rectal cancers with differences of 28 (95% CI: 26-30) and 27 (95% CI: [23][24][25][26][27][28][29][30][31] percentage points respectively, closely followed by ovarian cancer with a difference of 23 points (95% CI: 21-25). For distant liver cancer, there was no difference in survival by age (1-year RS = 14% in 50 to 64 age group and 75 to 84 age group).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For distant cancers, the greatest age-related differences in 1-year RS were observed for colon and rectal cancers with differences of 28 (95% CI: 26-30) and 27 (95% CI: [23][24][25][26][27][28][29][30][31] percentage points respectively, closely followed by ovarian cancer with a difference of 23 points (95% CI: 21-25). For distant liver cancer, there was no difference in survival by age (1-year RS = 14% in 50 to 64 age group and 75 to 84 age group).…”
Section: Resultsmentioning
confidence: 99%
“…Older adults may be less likely to receive curative treatment, [23][24][25][26][27][28][29] and especially in the face of uncertain prognosis, may be more likely to value quality of life over survival. 30 Second, in the context of a poor evidence base on treatment strategies in older adults, 31 the effectiveness and toxicity of treatment may differ across age groups. Evidence suggests higher posttreatment mortality and increased all-cause mortality in older patients, particularly in frailer ones.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research that has examined patient preference and refusal of cancer treatment in older adults has reported that older adults (as younger adults) prioritize quality of life and overall survival. 36 The most consistent determinant of refusal or acceptation of treatment was physician recommendation. 37 Further research on this would be useful to better interpret age-related disparities.…”
Section: Discussionmentioning
confidence: 99%
“…For shared decision making, knowing what matters most in life, rather than simply asking whether a patient would want a certain treatment, will give more clarity regarding treatments that should be considered or avoided for an individual patient [ 1 ]. To optimally counsel patients, it is important to know their priorities and how they value outcome options in relation to each other [ 2 ]. In a clinical setting, this also means understanding what quality of life means to the individual.…”
Section: Introductionmentioning
confidence: 99%